Customer loyalty to the retail pharmacy: Present and future of the Portuguese market - Pereira, L.; Quental, L.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Logistics Systems and Management, 2024)
Pharmacies should retain their customers to ensure their sustainability. The most relevant factors for this are store experience, technological evolution, digital presence, portfolio of services and quality of counselling. The analysis of the methodology was carried out by the 'Pereira problem solving research methodology' and with the research goals, it was intended to understand the causes of the lack of loyalty, the trend, loyalty strategies, its benefits, and the impact of the loss of proximity. The results allow us to understand that there is less customer loyalty. The main impact of the loss of proximity is the lack of pharmaceutical advice. The main reason for the lack of loyalty is the greater convenience in making purchases in other places. The best strategy to retain customers is to guarantee the quality of the counselling provided. There are benefits in this loyalty, like a greater knowledge of the customer's consumption history.